SEMANTIC PECULIARITIES OF CONSTRUCTIONS IN REFLEXIVE PRONOUNS IN MODERN RUSSIAN LANGUAGE (Proceedings of Southern Federal University. Philology, 2013)
Bunyaeva O. S.Keywords: reflexive pronouns, reflexives, co reference, semantic peculiarities, valence case, idioms, phraseology.Complex semantic processes which are viewed in the article occur in different types of structures with reflexive pronouns. The main point is to focus on semantics. New aspects of the study on reflexives are touched in the article. On the material of the reflexive pronouns we try to reveal some parts of language system where semantic shifts take place and new units are formed. Semantic patterns of building linguistic expressions are being examined and the list of units which include reflexives is being made.